Lipoprotein(a) carries triglyceride species associated with incident cardiovascular disease. - Takov,K; Penkov,S; Pechlaner,R; Elbahtety,E; Yap,LE; Schmidt,L; Berry,SE; Hall,WL; Singh,B; Willeit,J; Kiechl,S; Tsimikas,S; et al. (Atherosclerosis, 2026)
BACKGROUND AND AIMS: Lipoprotein(a) [Lp(a)] is described as a low-density lipoprotein-like particle, but recent work suggests heterogeneity, including triglyceride (TG)-rich features. We investigated whether native Lp(a) carries an apolipoprotein E (APOE)-associated TG signature, whether it is remodeled postprandially, and whether Lp(a)-associated TG species are linked to cardiovascular risk. METHODS: Plasma Lp(a) was immunocaptured under native conditions and analyzed by proteomics in patients with high Lp(a) (n=15) and lipidomics in healthy volunteers (n=9). Lp(a) produced in HepG2 cells was characterized using immunoprecipitation, density gradient ultracentrifugation, microsomal triglyceride transfer protein inhibition, and fatty acid loading. Matched fasting and postprandial samples assessed Lp(a) lipidome remodeling (n=6). The relationship between Lp(a)-associated TGs and cardiovascular risk was examined in the community-based Bruneck Study (n=623). RESULTS: Direct plasma Lp(a) immunocapture showed APOE enrichment, confirmed by proteomics, immunoblotting, reverse APOE immunocapture, and size-exclusion chromatography followed by Lp(a) immunoprecipitation. In vitro, HepG2 cells secreted APOE-containing Lp(a) that was more buoyant than apolipoprotein B (APOB)-only particles and less affected by lomitapide or fatty acid loading. The Lp(a) lipidome was more stable postprandially than plasma lipids. Plasma Lp(a) depletion reduced 35 lipid species, predominantly TGs, including TG(52:3) and TG(52:4), previously linked to incident cardiovascular disease. TG reduction following Lp(a) depletion correlated with attenuation of cardiovascular risk after Lp(a) adjustment in the Bruneck Study, supporting a clinically relevant TG signature of native Lp(a). CONCLUSIONS: Native plasma Lp(a) carries a defined TG signature that is relatively stable postprandially and linked to incident cardiovascular disease.